Enhancing Spiritual Intelligence Through Religious Mentorship: A Case Study at Al-Ishlah Elementary School - Khaeriyah, Umamatul; Nafi'a, Ilman; Gumiandari, Septi; Muhammad Fathi Ilmy (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study aims to explore the strategies used by religious mentors at Al-Ishlah Elementary School in fostering students' spiritual intelligence, identify the challenges they encounter, and examine the efforts made to overcome these barriers. Novelty: The research contributes to the limited empirical literature on spiritual intelligence development at the elementary level within Indonesian Islamic schools, emphasizing the unique role of religious mentorship in character formation and faith-based resilience. Methods: Using a qualitative descriptive approach, data were collected through in-depth interviews with one religious mentor and questionnaires administered to 36 students. Results: The findings reveal that students’ spiritual intelligence levels are predominantly “very high” (52.8%) and “high” (41.7%), indicating a generally strong spiritual foundation. Effective mentoring strategies include daily recitation of Asmaul Husna, congregational Dhuhr prayers, collective Yasin and istighosah, as well as Qur’anic literacy and memorization programs. Conclusions: Despite challenges such as limited concentration, Qur’anic fluency, tardiness, and time constraints, mentors effectively address these issues through psychological understanding, motivational reinforcement, open communication, and reward-based encouragement. The study underscores the vital influence of religious mentorship in nurturing students’ spiritual intelligence and holistic personal growth.